The Effectiveness and Complication Rate of Resorbable Biopolymers in Oral Surgery: A Systematic Review - Riccardo Fabozzi; Francesco Bianchetti; Domenico Baldi; Catherine Yumang Sanchez; Francesco Bagnasco; Nicola De Angelis (Dentistry Journal, 2025)
Background: Resorbable biopolymers are increasingly explored for use in regenerative procedures within dental surgery. Their ability to degrade naturally, minimize surgical reinterventions, and potentially reduce immunogenicity makes them appealing in guided bone and tissue regeneration applications. However, despite these advantages, uncertainties persist regarding their comparative effectiveness and associated risks. For example, polyethylene glycol (PEG)-based membranes have shown comparable outcomes to porcine-derived collagen membranes in bone regeneration procedures, yet studies have reported a higher incidence of soft tissue healing complications associated with PEG-based materials. Similarly, while polycaprolactone (PCL) and dextrin-based hydrogels have demonstrated promising clinical handling and bone fill capabilities, their long-term performance and consistency across different anatomical sites remain under investigation. These findings highlight the need for further well-powered clinical trials to establish standardized guidelines for their safe and effective use. Methods: A systematic review protocol was registered with the PROSPERO database and developed in alignment with PRISMA guidelines. Database searches were conducted in PubMed, Medline, Scopus, and Cochrane from June to December 2024. Only randomized controlled trials (RCTs) focusing on synthetic resorbable biopolymers in bone augmentation procedures were considered. Bias was evaluated using the Cochrane Risk of Bias tool. Results: Eleven RCTs were included, totaling 188 patients. The findings suggest that materials such as polylactic acid (PLA), polycaprolactone (PCL), and polyethylene glycol (PEG) contributed effectively to new bone formation. PEG-based membranes were found to perform on par with or occasionally better than traditional collagen membranes derived from porcine sources. Additionally, the application of 3D-printable polymers demonstrated promise in site-specific healing. Conclusions: Resorbable biopolymers are effective and safe for GBR procedures, with clinical outcomes comparable to traditional materials. Advances in 3D-printing technology and bioactive coatings may further enhance their regenerative potential. However, the incidence of soft tissue healing complications suggests the need for further long-term studies to optimize material properties and clinical application.